2016
DOI: 10.1111/jgs.14474
|View full text |Cite
|
Sign up to set email alerts
|

Life‐Space Mobility and Mortality in Older Women: Prospective Results from the Study of Osteoporotic Fractures

Abstract: Objectives To evaluate the relation between life-space mobility (extent, frequency, and independence of movement) and mortality in older women. Design Prospective cohort study. Setting Four U.S. clinical sites. Participants Women (N=1,498) aged 75–102 years (mean 87.6) followed from 2006–2015. Measurements Life-space during the past four weeks was assessed by interview, scored from 0 (daily restriction to bedroom) to 120 (daily trips outside town without assistance), and categorized (0–20, 21–40, 41–60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 36 publications
(95 reference statements)
1
47
0
Order By: Relevance
“…5 Life-space mobility measured by a multidimensional self-reported instrument, refers to a person's ability to move in their environment within a specific time period (e.g., within a day, week, or month), has been found to be associated with physical performance, disability, falls, fractures, physical activity, quality of life, and mortality. [6][7][8][9][10] Several studies have examined the effect of life-space mobility and cognitive function in non-Hispanic whites and African Americans. [11][12][13] For example, Crowe and colleagues found that greater life-space mobility was associated with reduced cognitive decline over 4 years of follow-up.…”
mentioning
confidence: 99%
“…5 Life-space mobility measured by a multidimensional self-reported instrument, refers to a person's ability to move in their environment within a specific time period (e.g., within a day, week, or month), has been found to be associated with physical performance, disability, falls, fractures, physical activity, quality of life, and mortality. [6][7][8][9][10] Several studies have examined the effect of life-space mobility and cognitive function in non-Hispanic whites and African Americans. [11][12][13] For example, Crowe and colleagues found that greater life-space mobility was associated with reduced cognitive decline over 4 years of follow-up.…”
mentioning
confidence: 99%
“…Most previous studies indicating the health benefits of going outdoors have measured going outdoors only by self-report (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Except for one study (25), the associations of objective outdoor time and health outcomes were examined using cross-sectional designs (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Since going outdoors does not require any special knowledge, motivation, cost, or time, it would be easier for older adults to incorporate going outdoors into their daily lives than other health behaviors such as exercise and smoking cessation. Previous studies have reported that going outdoors, housebound status, and life space are associated with various health outcomes, including mortality (8,9), instrumental/basic activities of daily living (10-13), cognitive function (14)(15)(16), and psychological health (10,17). Some studies have also indicated that influences of going outdoors on health outcomes differ with older adults' characteristics, such as gender (13); their belief in personal control (14); and physical status (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we list six public datasets that are used commonly in clinical studies and contain different types of clinical data (see Table 1). Some of them focus on specific diseases such as the Alzheimer's Disease Neuroimaging Initiative (ADNI) [69,70] , Osteoarthritis Initiative (OAI) [71] , and Study of Osteoporotic Fractures (SOF) [72] . Some of them collectd specific data type.…”
Section: Other Typesmentioning
confidence: 99%